Student Perceptions, English Reading Needs, and Learning Experiences in Inquiry-Based Blended ESP among Sharia Students - Yunika Triana; Pratomo Widodo; Kastam Syamsi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2026)
English reading is an important component of Islamic law education because it gives students access to international scholarship, legal terminology, and current debates on the subject. This study conducted a cross-sectional needs analysis of 271 students at the Faculty of Sharia of an Indonesian Islamic university. The dataset contained 43 complete four-point Likert items measuring the perceived value of English reading, self-assessed reading ability, career aspirations, preferences for inquiry-based methods, and preferences for online journal-based materials. The five dimensions showed high internal consistency, with Cronbach's alpha values ranging from .908 to .968. Career aspirations received the highest mean score (M = 3.30), whereas self-assessed reading ability received the lowest (M = 2.81), producing a .49-point gap on a four-point scale. Perceived value and journal-based material preferences were positively associated with self-assessed ability, whereas career aspirations showed a small negative association in the multivariable model. Welch’s tests found no significant differences between the English for Islamic Business Law and Literasi Digital classes. Interviews with four purposively selected students provided contextual accounts of journal reading, inquiries, and feedback. The results support an ESP curriculum that treats English reading as a faculty-wide need and uses inquiry, current journal articles, and staged reading support as design responses to that need.